Bioinformatics Analysis of the Ribosomal Proteins, RPL27, RPL37a and RPL41: 3-D Protein Modeling and Protein-protein Interaction Prediction - Chan, Stella Li Li; Sim, Edmund U. H. (International Journal of Bioscience, Biochemistry and Bioinformatics, 2013)
Ribosomal proteins (RPs) are constituents of ribosome important for protein biosynthesis but likely to have extraribosomal functions. Many RPs are associated with various diseases and cancers. A previous study reported RPL27, RPL37a and RPL41 gene to be downregulated in nasopharyngeal carcinoma (NPC) derived cell lines compared to their normal counterpart. However, their actual physiological roles in organogenesis or tumorigenesis have not been properly defined. In this paper, we report on the findings of structural prediction of these three genes and infer their interactions with other proteins using structural neighbor prediction and molecular docking strategies. Our results revealed that RPL27 interact with SYNJ2 and UBC9. RPL27 is predicted to mediate RNA binding protein and deregulate sumolyation. RPL37a is suggested to interact with CTNNB1, SCMH1 and ATBF1. It is predicted to deregulate Wnt degradation pathway, inhibit β-catenin migration and regulate homeotic transcription. Our studies on RPL41 did not allow logical inference on possible interacting factors. Nevertheless, results on RPL27 and RPL37a provide rational data for the elucidation of their molecular activities.